Rancang Bangun Dan Pembuatan Mesin Pembersih Pantai - Yuliarman, Yuliarman; Rahmatia Ikhsani, Siska; Effiandi, Nota; Zulhendri, Zulhendri; Yetri, Yuli (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The beach is a comfortable place for traveling and relaxing. Therefore, the cleanliness of the beach area must be maintained for the sake of mutual comfort. Due to the lack of discipline of visitors, a lot of rubbish is piled up and piled up out of place every day. So, cleaning staff find it difficult to clean up rubbish manually. Therefore, an initial design stage is needed, then proceed with the creation of a semi-automatic beach cleaning machine or Beach Cleaning Machine to overcome this problem. In the future, cleaning the beach using this machine can speed up the cleaning process and make the work of beach cleaners easier. The working principle of this machine uses a gasoline motor as a driving source. So, when the motorbike is turned on, the machine will work automatically. Then to direct the movement of the machine an operator is needed. So, it is very appropriate to use a Beach Cleaning Machine to clean the beach compared to picking it up directly or using manual tools, because it can save work time.